The importance of the hospital visit for the child with cancer and his companion - Carvalho, Regina Celi dos Santos (Seven Editora, 2023)
The hospital visit, in addition to being a noble mission, is an act of fraternal charity with patients. Hospitalization creates a disruption of the individual’s daily activities, depriving him of the accommodations of his home and forcing him to submit to different routines, with strangers. However, in these situations that generate discomfort and fear, the visit of a volunteer from the Gacc Support House (BA), in addition to the affective and emotional aspect, can contribute to a reduction in the degree of anxiety of the patient. DOI:https://doi.org/10.56238/uniknowindevolp-140